Characterization of nutrition-induced helix hand inversion of Bacillus subtilis macrofibers. - Wolfe, A J (1987)
The kinetics of Bacillus subtilis macrofiber helix hand inversion was examined. Inversion was induced by transfer of structures produced in one medium to another medium. When cultured at 20 degrees C in either medium, the doubling time was approximately 100 min. To establish a baseline, the macrofiber twist state produced in one medium was measured over the same time course during which other macrofibers underwent inversion after transfer to a second medium. The baseline was used to identify the time of inversion initiation: the point at which curves representing changes of twist as a function of time after transfer to the new medium intersected the baseline. Right- and left-handed macrofibers of different twists were produced by growth in mixtures of TB and S1 media. These were used to determine the influence of initial twist on the time course of inversion initiation. In the right to left inversion, a positive correlation was found between initial twist and the time of inversion initiation. The left to right inversion differed, however, in that a constant time was required for inversion initiation regardless of the starting left-handed twist. When a nutritional pulse was administered by transferring fibers from TB to S1 to TB medium, the time to initiation of inversion was found to decrease with incubation of increasing duration in S1 medium. A similar pulse protocol was used in conjunction with inhibitors to examine the protein and peptidoglycan synthesis requirements for the establishment of nutrition-induced memory that leads to initiation of inversion. Nutritionally induced right to left inversion but not left to right inversion required protein synthesis. The addition of trypsin to left-handed macrofibers apparently required, as described previously for the temperature-regulated twist system (D. Favre, D. Karamata, and N. H. Mendelson, J. Bacteriol. 164:1141-1145, 1985), for the production of left-handed twist states in the nutrition system.